Induksi platelet sebagai indikator komplikasi mikrovaskular pada penderita diabetes mellitus tipe 2 - Yulia Ramdhani; Ozar Sanuddin; Santi Syafril (Fakultas Kedokteran USU, 2013)
Introduction : Diabetes mellitus (DM) has been considered as a ‘‘prothrombotic state’ with enhanced platelet reactivity. Platelet activity and aggregation potential, which are essential components of thrombogenesis and atherosclerosis, can be conveniently estimated by measuring mean platelet volume (MPV) as part of whole blood count.This study was aimed to determine platelet indices [MPV, platelet distribution width (PDW) and platelet-large cell ratio (P-LCR)] between type 2 diabetics with and without microvascular complication.Methods : This study included 70 subjects with type 2 DM (40 with one or more microvascular complications) and 30 without microvascular complications. Anticoagulated blood (ethylene diamine tetracetic acid) was collected and analyzed in an automated blood cell counter for platelet count and indices.Results : In our study found the MPV, PDW and P-LCR were all significantly higher in subjects without microvascular complication compared to the subjects with microvascular complication [ 9.97 (SD 0.68) vs 9.81 (SD 0.76) fl ; 11.81 (SD 1.55) vs 11.44 (SD 1.50) fl ; 24.93 (SD 4.72) vs 23.79 (SD 4.88) % (P >0.05) ], respectively.Conclusion : There was no significant differences in platelet indices (MPV, PDW, and P-LCR) between subjects with and without microvascular complication.Keywords : mean platelet volume; platelet distribution width; platelet-large cell ratio; diabetes melitus; microvascular complication